2019
DOI: 10.12688/f1000research.16701.1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular regulation of arteriovenous endothelial cell specification

Abstract: The systemic circulation depends upon a highly organized, hierarchal blood vascular network that requires the successful specification of arterial and venous endothelial cells during development. This process is driven by a cascade of signaling events (including Hedgehog, vascular endothelial growth factor (VEGF), Notch, connexin (Cx), transforming growth factor-beta (TGF- β), and COUP transcription factor 2 (COUP-TFII)) to influence endothelial cell cycle status and expression of arterial or venous genes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 89 publications
2
31
0
Order By: Relevance
“…To form a functional blood circulatory system, primordial endothelial cells must be specified into arterial and venous fates (43). Arterial and venous blood vessels have different functions within the circulatory network, and the endothelial cells that line arteries and veins reflect those differences in gene expression, structure, and response to cytokines and growth factors (44,45).…”
Section: Arteriovenous Endothelial Cell Specificationmentioning
confidence: 99%
“…To form a functional blood circulatory system, primordial endothelial cells must be specified into arterial and venous fates (43). Arterial and venous blood vessels have different functions within the circulatory network, and the endothelial cells that line arteries and veins reflect those differences in gene expression, structure, and response to cytokines and growth factors (44,45).…”
Section: Arteriovenous Endothelial Cell Specificationmentioning
confidence: 99%
“…One hypothesis is that Dach1 induces the expression of arterial EC fate determinants in all capillary ECs. Notch transcription factors are the most well recognized artery cell fate determinants described to date (Fang & Hirschi, 2019). In examining differentially expressed genes (DEGs; LogFC > 0.25) between Dach1 OE and control in each cluster, we found that Dach1 does not broadly change the level of Notch pathway genes, or any other validated artery marker, in capillary subpopulations even though it was overexpressed in virtually all ECs ( Fig.…”
Section: Dach1 Shifts the Endothelial Specification Trajectory Towardmentioning
confidence: 87%
“…Blood vessels arise early during embryogenesis to compensate for the increasing need of nutrients and oxygen of the growing and differentiating organs. Vasculogenesis, the de novo formation of blood vessels in embryo, is different from angiogenesis [83][84][85]. Whereas angiogenesis is the formation of blood vessels from existing ones, vasculogenesis is the process of differentiation of angioblasts as they coalescence to form the primitive vessel bed and is limited to the embryonic phase.…”
Section: The Vein Identity and The Link To Notchmentioning
confidence: 99%
“…Venous and lymph markers appear later, usually after day E9-9.5 [85]. Despite the different morphology origin, vasculogenesis and angiogenesis are regulated by similar mechanisms with major players being the Notch signaling pathway and VEGF; other pathways involved are BMP/TGF-β and Hedgehog (HH) [84,85].…”
Section: The Vein Identity and The Link To Notchmentioning
confidence: 99%
See 1 more Smart Citation